2018
DOI: 10.5539/ijc.v10n4p130
|View full text |Cite
|
Sign up to set email alerts
|

The Capping Theory of Chemical Clusters Based on 12N/14N Series

Abstract: The genesis of chemical clusters of the transition and main group elements has been established. The base-line for cluster valence electrons has been demarcated with help of capping series. Using the base-line as a reference, the formulas of fragments and clusters were generated.  Also a simple general formula for calculating cluster valence electrons for systems ranging from a single to multi-skeletal element clusters was identified. The concepts of the existence of nuclei in clusters and some having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…When the sequence of the K(n) parameters and their corresponding cluster valence electrons, it was found that they form well-organized sequence of INFINITE ARITHMETICAL PROGRESSIONS with no beginning and no end [12,13].…”
Section: S=ve=14n+qmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sequence of the K(n) parameters and their corresponding cluster valence electrons, it was found that they form well-organized sequence of INFINITE ARITHMETICAL PROGRESSIONS with no beginning and no end [12,13].…”
Section: S=ve=14n+qmentioning
confidence: 99%
“…Skeletal numbers are very easy and quick in categorizing a given chemical cluster from the main group or transition metals [10][11][12][13][14]16]. A cluster formula is decomposed usually into a whole number using skeletal elements.…”
Section: Categorization Of Clusters and Cluster Clan Treesmentioning
confidence: 99%
“…Relatively recently, skeletal numbers were developed for the periodic table elements of the main group as well as the transition metals and ligands [10,11]. The skeletal numbers have been extremely useful in analyzing and categorizing clusters into CLANS and FAMILIES [12,13]. What is interesting is that using skeletal numbers a cluster formula with or without ligands is decomposed into a whole number, given the symbol ii.…”
Section: Introductionmentioning
confidence: 99%
“…In chemistry, some clusters have been categorized as closo, nido, arachno, hypho and klado, among others [1][2][3][4][5][6][7]. In this regard, the polyhedral skeletal electron pair theory (PSEPT) has been extremely useful in this process [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For categorization of clusters, it was found to be more convenient to utilize the S=4n+q for both main group and transition metal clusters except when the cluster valence electrons are being calculated whereby S=14n+q is applied for transition metal clusters [3,4]. The skeletal numbers which were derived from the series have been found to be extremely useful in the derivation of chemical graph theory and equations for calculating cluster valence equations [6]. In addition, they can be used as a guide to predict the possible geometrical and graphical structures of clusters [6].…”
Section: Introductionmentioning
confidence: 99%